2017
DOI: 10.1590/1982-0224-20160039
|View full text |Cite
|
Sign up to set email alerts
|

Variation in male reproductive system characters in Corydoradinae (Loricarioidei: Callichthyidae) reflects the occurrence of different lineages in this subfamily

Abstract: Callichthyidae comprises a well-corroborated monophyletic group divided into two subfamilies: Corydoradinae and Callichthyinae. A recent proposal, based on molecular data, suggests that Corydoradinae is composed by nine monophyletic lineages, possibly genera. The species pertaining to those lineages have extensive modification in the size of genome, including diploid, tetraploid and octoploid species. Considering the occurrence of these monophyletic lineages and that the variations in DNA content may imply in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…They reported that the bilateral testes of Nile fish were suspended from the dorsal portion of the body cavity, ventral to the kidneys. The location and portion of the seminal vesicles observed in this present study were similar to the report of Mazzoldi et al (2007) and Spadella et al (2017) in Callichthyidae family with the secretory activity occurring in the caudal portion with or without the seminal vesicles. Also in the families of Heteroneustidae, Clariidae and Auchenipteridae seminal vesicles occur in the caudal region of the reproductive system, as reported by Meisner et al (2000).…”
Section: Gross Morphometrysupporting
confidence: 90%
“…They reported that the bilateral testes of Nile fish were suspended from the dorsal portion of the body cavity, ventral to the kidneys. The location and portion of the seminal vesicles observed in this present study were similar to the report of Mazzoldi et al (2007) and Spadella et al (2017) in Callichthyidae family with the secretory activity occurring in the caudal portion with or without the seminal vesicles. Also in the families of Heteroneustidae, Clariidae and Auchenipteridae seminal vesicles occur in the caudal region of the reproductive system, as reported by Meisner et al (2000).…”
Section: Gross Morphometrysupporting
confidence: 90%
“…Males specimens exhibit a genital papillae with a tubular shape as most species of Corydoradinae and most species of lineage 6 [22]. Males are generally smaller than females with a darker color pattern tending to form clear longitudinal irregular lines on the laterals of the body vs .…”
Section: Resultsmentioning
confidence: 99%